التقانات اللغوية التركيبية الحديثة: آليات تحويل النص العربي إلى كلام منطوق Modern synthetic linguistic technologies: Arabic text to speech mechanism - Khalifa, Othman Omran; Obaid, Mustafa Zeki; Adam, Zalika; Nasser, Youcef (The Korean Association of Arabic Language and Literature, 2019)
في ظل تطور تقانات الحاسوب وتنامي أدوات الاتصال والتواصل، باتت الحاجة إلى استخدام الحاسوب في الكثير من التطبيقات الحيوية أكثر أهمية من ذي قبل؛ حيث استحالت إلى تطبيقات مفيدة وجيدة في كثير من مجالات الحياة العامة والخاصة على سواء. إذ نلفي، في حالات، أن استيعاب النص المسموع يفوق استيعاب النص المقروء عبر الوسائل والتقانات المهمة لمساعدة من يعاني من إجهادات وصعوبات في القراءة. ولمـا كـان التواصل الكلامي أسهل وأنجع أنواع التواصل، فإنه يجرى العمل حاليًا على إنشاء جيل مـن الحواسيب في مكنتها التواصل كلاميًا مع المستخدم؛ حيث تأتي أنظمة توليد الكلام في مقدمة هذه المجالات الحيوية. إن الهدف من عملنا هذا، هو الوقوف على اللسانيات الحاسوبية العربية بحثًا وتطبيقًا على أمل المساعدة على كيفية استخدام اللغة العربية لدخول مجتمع المعرفة. ومما لا شك فيه أن التعددية اللغوية باتت واقعًا مفروضًا ومكشوفًا في كل المجتمعات الدولية، لكن ليس على حساب اللغة العربية في المناطق العربية؛ مما يفترض إيلاءها الأهمية الكبرى رغبة من محبيها ومتقنيها بهدف تطويرها ومواكبتها عصر التقانات الحديثة. The development and growth of information and communications technologies led to the use of digital era in many vital applications in our daily life that require human-machine interaction. As verbal communication is the easiest and most effective communication, a generation of technologies are being created to enable communication with the user. Speech-generation systems come at the forefront of these vital areas. However, most of the available Arabic Text To Speech Systems have drawbacks such as discontinuity, limited vocabulary and poor naturalness. The purpose of this work is to identify the Arabic linguistics technologies in research and application in the hope of helping how to use the Arabic language to enter the knowledge society. There is no doubt that multilingualism has become an imposed reality in all international societies, but not at the expense of the Arabic language in the Arab regions. This is supposed to give great importance to the desire of its fans and technocrats to develop and cope with the age of modern technologies.